A Simplified Inversion Technique for the Frozen Elephant Trunk Procedure Using a Four-Branched Graft - Kim, Jae Hyun; Na, Chan-Young (The Thoracic and Cardiovascular Surgeon, 2013)
During the frozen elephant trunk (FET) procedure using a four-branched graft, making a distal anastomosis between the noninverted proximal graft and the distal stented aorta is quite challenging and takes time. Here, we introduce a simplified inversion technique for the FET procedure that uses a four-branched graft. This technique makes the distal anastomosis easy and secure, which would contribute to decreasing the circulatory arrest and ischemic time.
Keywords: aorta/aortic; endovascular procedures/stents; surgery/incisions; surgical equipment